Based on SEER Database: Population Distribution, Survival Analysis, and Prognostic Factors of Organ Metastasis of Lung Large Cell Neuroendocrine Carcinoma - Liu, Chang-fu; Tao, Yu-jian (Frontiers in Oncology, 2022)
【Abstract】 Background The incidence rate of lung Large Cell Neuroendocrine Carcinoma (LCNEC) in lung cancer is low, but the malignancy is high and the prognosis is poor.We used the Surveillance, Epidemiology, and End Results(SEER) database to determine the population distribution of organ metastasis in LCNEC, conduct survival analysis, judge prognostic factors, and provide direction for follow-up diagnosis and treatment. Materials and methods By logging into the SEER database, the data of lung large cell neuroendocrine carcinoma were retrieved and the target population was selected. According to the presence or absence of organ metastasis (bone, brain, liver and lung), we divided the target population into no organ metastasis group (n = 1202) and organ metastasis group (n = 870). By analyzing the clinicopathological data of patients and using the survival function, the corresponding median survival time was obtained, and the influencing factors of each group were analyzed. Then, the significant influencing factors were analyzed by multivariate cox regression analysis, to screen out the independent influencing factors. Result In the overall sample group, multivariate cox regression analysis showed that sex, age, primary site surgery, bone metastasis, brain metastasis, liver metastasis, radiotherapy and chemotherapy were independent prognostic factors.The 1-year survival rate was 13.8% in the bone metastasis group, 19.1% in the brain metastasis group, 13.8% in the liver metastasis group and 20.3% in the intrapulmonary metastasis group. In the organ metastasis group, multivariate cox regression analysis showed that sex, chemotherapy, radiotherapy sequence with surgery,primary site surgery, liver metastasis and age at diagnosis were independent factors affecting the prognosis. Conclusion In the overall sample of LCNEC, bone metastasis, brain metastasis and liver metastasis all reduced the overall survival time, while the effect of intrapulmonary metastasis on the overall survival time was not statistically significant. Sex, chemotherapy, radiotherapy sequence with surgery, primary site surgery, liver metastasis and age were independent factors affecting the prognosis of the LCNEC organ metastasis group.Women, chemotherapy and radiotherapy sequence with surgery were favorable factors, while old age, liver metastasis and male were unfavorable factors.